CGIAR Livestock Fish Mega Program can 'do something special' - Hall, S. (International Livestock Research Institute, 2010)
Steve Hall, Director General of the WorldFish Centre reflects on the CGIAR Livestock Fish Mega Program stakeholder meeting. It was a good opportunity to think through how CGIAR centers together “can really make a difference in some selected locations where there’s an opportunity to substantially increase the supplies of fish, meat, milk, and eggs for poor people.” He was speaking in the margins of the CGIAR Livestock Fish Mega Program stakeholder consultation meeting in Addis Ababa, 24 and 25 August 2010.